2020
DOI: 10.1016/j.agrformet.2019.107784
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of a super-typhoon on Hong Kong's secondary vegetation and recommendations for restoration of resilience in the forest succession

Abstract: Impact assessment of a super-typhoon on Hong Kong's secondary vegetation and recommendations for restoration of resilience in the forest succession. Agricultural and Forest Meteorology, 280. a107784.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…For both VIs, less than 9% of the cells of the FEF were hit by all of the five typhoons examined (Table S4), and the small size of the FFDP relative to the FEF certainly limit its ability to capture cells with high typhoon frequencies Figure 6). Effects of topography on the cyclone damage distribution within forested landscapes are widespread across regions affected by tropical cyclones [23,75,76]. In this study, elevation was the only topographical variable that correlated with typhoon damages for three of the five studied typhoons, although relationships were weak (ρ < 0.2).…”
Section: Typhoons Damages Intensity In the Plot And The Reservementioning
confidence: 49%
“…For both VIs, less than 9% of the cells of the FEF were hit by all of the five typhoons examined (Table S4), and the small size of the FFDP relative to the FEF certainly limit its ability to capture cells with high typhoon frequencies Figure 6). Effects of topography on the cyclone damage distribution within forested landscapes are widespread across regions affected by tropical cyclones [23,75,76]. In this study, elevation was the only topographical variable that correlated with typhoon damages for three of the five studied typhoons, although relationships were weak (ρ < 0.2).…”
Section: Typhoons Damages Intensity In the Plot And The Reservementioning
confidence: 49%
“…Topographic factors such as elevation, slope and aspect were reported to significantly affect the forest damage caused by typhoons/hurricanes [1,6,23,38,39]. These data can be derived from the digital elevation model (DEM) data.…”
Section: Topographic and Climatic Datamentioning
confidence: 99%
“…In addition, many previous studies have also indicated that climatic factors, such as wind velocity and rainfall, affect the impact of typhoons/hurricanes on forest damages [1,6]. Therefore, we used wind velocity and rainfall as input variables in the RF model to monitor forest damage.…”
Section: Topographic and Climatic Datamentioning
confidence: 99%
See 2 more Smart Citations